Effects of active packaging on the physico-chemical properties of fresh-cut cantaloupe (Cucumis Melo L. Var. Glamour) - Kamaruddin, Syahidah; Shamsuddin, Rosnah; Ahmedov, Anvarjon; Othman, Zaulia; Mohd Adzahan, Noranizan (2014)
One of the most well-known active packaging concepts is gas absorbers or scavengers. In this study, modified atmosphere packaging was developed to investigate the physico-chemical properties of fresh-cut cantaloupe (Cucumis Melo L. Var. Glamour) fruit during storage by using oxygen and ethylene absorbers. The freshcut cantaloupes were cut into small cubes and immersed in a calcium lactate solution (1%) prior to packing in polypropylene (PP) container that contained ethylene and oxygen absorbers and sealed with low-density polyethylene (LDPE) films. The changes in physico-chemical properties of the packed fruits were determined in terms of colour, pH, texture and total soluble solid (TSS) during storage for 18 days at 2 ºC with 87% relative humidity (RH). No overall significant changes (p<0.05) were observed on the colour and pH properties of the fresh-cut cantaloupes in all packages. The freshcut cantaloupes packed with ethylene absorber in the PP container demonstrated better firmness than ethylene/oxygen absorbers and control packages. The total soluble solid (TSS) of the fruits in the ethylene and ethylene-oxygen absorbers packages were well preserved compare to the control package. These findings indicate that the shelf life of fresh-cut cantaloupes was extended to a certain period of time due to the presence of the gas absorbers.